A New Approach for Synthesis of Low‐moisture Glycidyl Azide Polymer. Issue 11 (22nd May 2019) - Abdelhafiz, Mahmoud; Elbeih, Ahmed
Abstract : In this work, low‐moisture glycidyl azide polymer (GAP) was successfully prepared using a modified two‐step method. The modified method resembles the structure of the classical two‐step method, which is widely used to prepare the GAP. Firstly, epichlorohydrin (ECH) is polymerized into polyepicholorohydrin (PECH), which is subjected afterward to azidation step using sodium azide (NaN3 ). Interestingly, minimizing the water content in the final GAP product, which is a challenging when dealing with GAP as a rocket propellant binder, was effectively achieved by utilizing low boiling point solvents instead of the relatively high boiling point Dimethyl formamide (DMF), monitoring the volatility of ECH and controlling the exothermicity of the reaction. Prepared GAP samples were investigated using Fourier transformer infra‐red (FT‐IR), gel‐permeation chromatography (GPC) and elemental analysis apparatus (CHNS) were used to characterize the product. The moisture % in the final product was examined using the Karl‐Fisher Technique. Results showed the successful preparation of GAP with low water content (<0.01 %), high average molecular weight (> 2000 g· mol –1 ), 42.82 % nitrogen, a viscosity of 3484 cP at 20 °C, yield ranges between 95–98 % and a polydispersity index of 1.2. The prepared GAP is promising for replacement of the classical GAPs in the energetic materials applications. Abstract :